Cardiotonics. Cardiac glycosides. Antiarrhythmic drugs - Doroshenko, Oksana (My University, 2021)
The lecture contains description of main inotropic and antiarrhythmic preparations which are used in therapy of congestive and acute heart failure and different types of arrhythmia.
Keywords: pharmacology; inotropic drugs; cardiac glycosides; digitoxin; dobutamin; antiarrhythmic drugs; lidocain; amiodaron; heart failure; verapamil